GE_GERICHTE P/18613/2018 vom 15. November 2022 - GE Cour de justice (2022)
VIOLENCE CONTRE LES AUTORITÉS;EXCUSABILITÉ;VIOLATION DE DOMICILE;LÉSION CORPORELLE;ABUS D'AUTORITÉ | CP.285; CP.14; CP.186; CP.123; CP.312